The Combination of Indigofera Leaf and Corn as Fermented Feed on the Growth of Arabic Chicken (Gallus turcicus) - Zulkifli zulkifli; Mustaqim mustaqim; Ulfatulhasanah; Mida Wahyuni (Warmadewa University Press, 2021)
This study aims to find out the effect of combination of fermented Indegofera leaf and corn on the growth of Arabic chicken. This study used a completely randomized design (CRD) with 4 treatments and 3 replications. The treatment consisted of P.1: Commercial Feed; P.2: 80% Indegofera sp leaves + 20% Corn; P.3: 70% Indegofera leaves + 30% Corn; P.4: 60% Indegofera leaves + 40% Corn. Measurement of Arab chickens weight was carried out once a week for one month. The weight data were analyzed using one-way analysis of variance (ANOVA) followed by Duncan's test. The results showed that the combination of fermented feed consisting Indegofera sp leaves and corn had a significant effect (P<0.05) on the growth of Arab chickens. The conclusion shows that fermented feed of Indegofera leaves sp and corn as chicken diet could improve the growth of Arabian chickens.